Study on the physical meaning of seismic inhomogeneous degree by rock fracture experiments - 李志雄 马胜利 李圣强 李闽峰 路鹏 陈华静 王松 吴婷 (Acta seismologica sinica, 2005)
It is observed that the parameter of seismic inhomogeneous degree (GL value) calculated from the earthquake catalog shows obvious abnormal changes prior to strong earthquakes, indicating the state change of local seismic activity. This paper focuses on the mechanism for the abnormal changes of the GL values based on the sequences of acoustic emission for three types of rock samples containing macro-asperity fracture; compressional en-echelon fracture and model-III shear fracture. The results show that for the three types of rock samples, there are continuous abnormal changes of GL value (>1) just before the non-elastic deformation occurs or during the process of nucleation prior to the instability. Based on the experimental results, it seems that the process of creep sliding and resistance-uniformization along fault zone is the possible mechanism for the abnormal changes of GL value before rock fractures.[PUBLICATION ABSTRACT]